2020
DOI: 10.1093/jac/dkaa121
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of R-type pyocins against Pseudomonas aeruginosa on biofilms and in a murine model of acute lung infection

Abstract: Background The appearance of MDR strains and the development of biofilms make Pseudomonas aeruginosa infections a therapeutic challenge. To overcome this scenario, bacteriocins have been proposed as a potential adjuvant or alternative to antibiotic treatment. Objectives To study the activity of R-pyocins on biofilms and in a murine model of pneumonia using a high-risk clone of P. aeruginosa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…When the 32 clinical isolates were tested against the 32 isolated pyocins, none were able to lyse the source strain or those strains with the same serotype or ST. As previously described, variability in the susceptibility to the pyocins was observed between those isolates that shared ST and/or serotype and the same type of pyocin, probably due to the frequently observed mutations in the LPS genes in CF, affecting recognition by the RBP 3 , 29 , 30 . Pyocins have been considered potential alternatives to antibiotics, and several studies have demonstrated antimicrobial activity of pyocins alone or in combination with other antimicrobials and those sharing the LPS as target 13 , 22 , 23 , 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…When the 32 clinical isolates were tested against the 32 isolated pyocins, none were able to lyse the source strain or those strains with the same serotype or ST. As previously described, variability in the susceptibility to the pyocins was observed between those isolates that shared ST and/or serotype and the same type of pyocin, probably due to the frequently observed mutations in the LPS genes in CF, affecting recognition by the RBP 3 , 29 , 30 . Pyocins have been considered potential alternatives to antibiotics, and several studies have demonstrated antimicrobial activity of pyocins alone or in combination with other antimicrobials and those sharing the LPS as target 13 , 22 , 23 , 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall our findings highlight that clinical populations of P. aeruginosa exhibit a heterogenous response to R-pyocins and that this likely extends to any antimicrobial that utilizes the LPS. A number of LPS- and saccharide-binding phage have been identified and tested as antimicrobials against P. aeruginosa (24, 102108) and other types of LPS-specific antimicrobials, including R-pyocins, are also being considered as treatments (12, 13, 37, 38, 109, 110). Our work implies that treatment with alternative therapies utilizing the LPS may not eradicate strains within infections completely, potentially leading to highly resistant isolates taking over.…”
Section: Discussionmentioning
confidence: 99%
“…A strain may be susceptible or resistant to any variation of the different R types, but are generally thought to be resistant to the subtype they produce (19,20,42). R-pyocins have previously been explored as potential therapeutics (28,51,52), but little is known about their binding to target cell receptors, or their killing efficacy in heterogenous populations of P. aeruginosa. It is known that multiple isolates sourced from populations of P. aeruginosa from CF lungs exhibit considerable variation in susceptibility to antibiotics (2,15,(53)(54)(55)(56), however heterogeneity in R-pyocin susceptibility, or susceptibility to other types of bacteriocins has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our findings highlight that clinical populations of P. aeruginosa exhibit a heterogenous response to R-pyocins and that this likely extends to any antimicrobial that utilizes the LPS. A number of LPS-and saccharide-binding phage have been identified and tested as antimicrobials against P. aeruginosa (24,(92)(93)(94)(95)(96)(97)(98), and other types of LPS-specific antimicrobials, including R-pyocins, are also being considered as therapeutics (12,13,37,38,99,100). Our work implies that treatment with alternative therapies utilizing the LPS will not eradicate strains within infections completely, potentially leading to highly resistant isolates taking over.…”
Section: Figmentioning
confidence: 99%
“…Several monosaccharide residues on the outer core of the LPS have been proposed to confer susceptibility and specificity to some of the R-pyocin types (24,25); however, only the receptor of the R3-type pyocin has been clearly defined to be the Glc IV terminal glucose on the outer core of the LPS (26). R-pyocins have previously been explored as potential therapeutics (12,13,37,38), but little is known about their binding to target cells or their killing efficacy in heterogeneous P. aeruginosa populations.…”
mentioning
confidence: 99%